Web Based Tuition Payment Information System SMS Gateway Based Response Automation (Study at Walisongo Vocational School, Semarang) - Fujiama D. Silalahi; Irwan Aji Mahendra (Journal of Technology Informatics and Engineering, 2023)
At the Walisongo Vocational School Semarang Semarang SPP payment system that is carried out at this time is by manual method where payment of SPP is still conventional where administrative staff must look for student data and record transactions in the ledger containing student data, then fill in the student payment card column. and come as proof that students have paid. However, the payment system is less optimistic.Seeing these situations and conditions, the author makes a web-based response system for spp payment automation based on the SMS gateway at Walisongo Vocational School Semarang by using the Research And Development (R & D) method where this application can help administrative administrators in this institution to facilitate payment and can make notifications directly to parents of students automatically.This application the author uses the HTML and PHP programming language with the MySQL database, where later the data will be entered and stored in the database and the author also uses the SMS gateway hardware as a notification media to the parents of students so that the use can be more easier and optimal.